732 views
0 votes
Which expression is equivalent to (8^2)-4 ??

A. 1/8^2
B. -1/ 8•8•8•8•8•8•8•8
C. 1/8•8•8•8•8•8•8•8
D. 8^2

User Crusaderky
by
4.9k points

2 Answers

0 votes

Answer:

C

Explanation:

User Rifa Achrinza
by
6.1k points
5 votes

Answer:

Option C
(1)/(8*8*8*8*8*8*8*8)

Explanation:

we have


(8^(2))^(-4)

Remember that


(a)^(-b) = (1)/(a^(b))


(a^(b))^(c)=(a)^(b*c)

therefore


(8^(2))^(-4)=(8)^(-4*2)=(8)^(-8)


(8)^(-8) = (1)/(8^(8))


(1)/(8^(8))=(1)/(8*8*8*8*8*8*8*8)

User John Noonan
by
5.2k points